PENGARUH WORD OF MOUTH (WOM) DAN ATRIBUT PRODUK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE VIVO MELALUI BRAND IMAGE - Dewi Kurniawati; Rina Eka Pertiwi; Fatima Tuzzahra Alkaf; Lazarus Sinaga (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2022)
Smartphones are one of the technologies that cannot be separated from the lives of consumers, such as those in Indonesia. The purpose of this study was to see the effect of word of mouth and product attributes on purchasing decisions through the brand image of Vivo smartphones. This research category is analytical descriptive using Path Analysis as an analytical technique. Respondents in this study were students of the Faculty of Economics and Business, Pancasila University, Special Regular Class Class 2018-2020 with a total of 66 students. From the estimation results, it is found that consumer buying decisions on smartphones are influenced by word of mouth and product attributes received by consumers through the smartphone brand image. Based on the results obtained, brand image is directly influenced by word of mouth, product attributes, and purchasing decisions. Meanwhile, indirectly, word of mouth does not affect purchasing decisions through the Vivo smartphone brand image, because consumers trust consumer reviews of smartphone users more than the smartphone brand image. Meanwhile, Vivo smartphone product attributes indirectly influence purchasing decisions through brand image. Therefore, to be able to influence purchasing decisions, Vivo smartphones must maintain product quality in accordance with current consumer needs, especially among students.